CONVERSATION IMPLICATURE OF ARSY AND ARSYA IN YOUTUBE CHANNEL - Nia . Auliyah; Sumarsih . .; Amrin . Saragih (Universitas Negeri Medan, 2021)
ABSTRACTThe aims of this study were to describe the kinds of Conversational Implicarture, to explain the ways of performing implicature and to describe the contex of implicature by Arsy And Arsya in Youtube channel. This research was conducted by using qualitative descriptive design. The data were the utterences of Arsy and Arsya in Youtube Channel. The data analyzes by using theory of conversational implicature.the result of this study were 1) the kinds of conversational implicatures used by Arsy and Arsya found in the text, they are Qualitative Maxim, Quantitative Maxim, Relevant Maxim, and Mannner Maxim. The analysis has found that Quantitative appeares in Arsy and Arsya YouTube Channel. (2)The process of conversational implicatures used by Arsy and Arsya in Wonderland YouTube Channel is realized through politeness strategies. (3) The reasons of the realization of conversational implicatures used by Arsy and Arsya in Wonderland YouTube Channel is realized through the system of tenor formed as [unequal/informal/positive/frequent]. It is found that there are are four. They are involved Bald on Record, Positive Politeness, Negative Politeness, and Off the Record. Off the record is the higher result found. Since she give codes to the hearer to get what her intentions, and it sometimes coded by gesture. . While in Arsya’s utterances, the types of politeness implicatures found are three. They are involved Bald on Record,Positive Politeness, and Off the Record. Off the record is the higher result found. Since she give codes to the hearer to get what her intentions, and it sometimes coded by gesture. Keywords: Implicature, Conversational Implicatur, Politeness, Tenor, Interaction